Martin rising : requiem for a King - Pinkney, Andrea Davis (Scholastic Press, 2018)
Presents a collection of poetry and paintings, highlighting the final months of Martin Luther King, Jr.'s life. Includes a brief informational section highlighting King's life and the plight of sanitation workers whose march he was planning to attend when he was assassinated. Includes a timeline and archival photographs.